“Prevención de riesgos y desastres naturales en la escuela” - Quingatuña Bonilla, Jessica Jenibeth (2024)
Society, in general, is not exempt from suffering the consequences of natural disasters, which is why Ecuador today, more than ever, is waiting for what may happen with the permanent threat of the Cotopaxi volcano. Therefore, the project intends to reduce the risk that this problem may cause in the educational population, where the prevention of risks and natural disasters has a significant importance in the education of students who experience this problem since it affects them physically, psychologically, and intellectually. The research aims to establish natural disaster risk prevention focused on the threat of the eruption of the Cotopaxi volcano through a plan of conferences with experts to safeguard the integral health of the educational community. The methodology was based on the interpretive paradigm because it allowed us to understand the reality of the research problem; the research approach is qualitative, for the collection of information from different bibliographic sources through websites, scientific articles, journals, books, blogs, and repositories, which contributed to the development of the theoretical framework, the comparative method was established to contrast the theories between prevention and natural disasters, in addition, the type of research is documentary bibliographic carrying out a process of analysis to establish conclusions and recommendations. The conclusion is that natural disasters are problems that affect the learning process, which poses significant challenges for students in adapting to different risk prevention mechanisms so that this will reduce the state of vulnerability in the event of a catastrophic event in the event of the eruption of the Cotopaxi volcano.